2008
DOI: 10.1016/j.cognition.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Data from eye-tracking corpora as evidence for theories of syntactic processing complexity

Abstract: We evaluate the predictions of two theories of syntactic processing complexity, dependency locality theory (DLT) and surprisal, against the Dundee corpus, which contains the eye-tracking record of 10 participants reading 51,000 words of newspaper text. Our results show that DLT integration cost is not a significant predictor of reading times for arbitrary words in the corpus. However, DLT successfully predicts reading times for nouns and verbs. We also find evidence for integration cost effects at auxiliaries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
548
7
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 451 publications
(594 citation statements)
references
References 34 publications
(55 reference statements)
35
548
7
4
Order By: Relevance
“…Previous results have indicated that the reading time of a word may be correlated with its position in the sentence (Ferreira & Henderson, 1993;Demberg & Keller, 2008a), which would confound any findings that adding material can speed processing a subsequent verb (and which might indeed confound previous reports of anti-locality effects such as Konieczny, 2000). 6 We address this confound by including additional material preceding the main clause: a subordinate clause with a dative-taking optionally ditransitive verb.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous results have indicated that the reading time of a word may be correlated with its position in the sentence (Ferreira & Henderson, 1993;Demberg & Keller, 2008a), which would confound any findings that adding material can speed processing a subsequent verb (and which might indeed confound previous reports of anti-locality effects such as Konieczny, 2000). 6 We address this confound by including additional material preceding the main clause: a subordinate clause with a dative-taking optionally ditransitive verb.…”
Section: Methodsmentioning
confidence: 61%
“…Locality effects have been observed for a range of different constructions in English (Gibson, 1998), while expectation effects (also known as anti-locality effects when the issue is the effect of pre-verbal dependents on verb processing times) have been reported for German, Japanese, and Hindi (Konieczny, 2000;Konieczny & Döring, 2003;Nakatani & Gibson, 2008;, and more recently also for English (Demberg & Keller, 2008a;Jaeger et al, 2008). However, ours is the first demonstration to our knowledge that both expectation and locality effects can occur in the same structure in the same language, and that the two effects interact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious question is why we did not observe surprisal effects in the eyetracking measures given past reports of surprisal effects on reading time (Boston et al, 2008;Demberg and Keller, 2008;Demberg et al, 2013;Levy, 2008). It is important to note, however, that these earlier studies investigated either overall surprisal (i.e., a combination of n-gram and lexicalized syntactic surprisal) or un-lexicalized part-of-speech (POS) surprisal, both of which are different from the surprisal measure we investigated.…”
Section: Discussionmentioning
confidence: 84%
“…Surprisal is an information-theoretic concept that reflects the expectedness of each word given its preceding context. Surprisal is an increasingly influential concept in the language sciences because it reflects moment-by-moment processing operations related to the system's attempts to connect the current input to the left context, based on the comprehender's history of language use (Boston et al, 2008;Demberg and Keller, 2008;Hale, 2001;Levy, 2008). Unlike some other measures of text complexity, a surprisal value can be generated for every word of a text, making it methodologically feasible to relate syntactic difficulty to brain activity on a word-by-word basis during the reading of connected texts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation